Motivasi Belajar di Pascasarjana dalam Komparasi Perspektif Mahasiswa Freshgraduate dan Mahasiswa Berpengalaman Kerja - Afkarina, Miftahul (Jurnal Ilmiah Dikdaya, 2025)
This research is a qualitative study that objectively describes the real state of the events being investigated. This study uses interview techniques to obtain data from the subjects being studied. The research was conducted on college students in East Java using random sampling techniques. The focus of this research is to examine and discuss the learning motivation of students to continue their education to the postgraduate level from two groups: fresh graduates and students with work experience. Learning motivation is a student's tendency to engage in learning activities driven by the desire to achieve the best possible learning outcomes. Learning motivation comes from within oneself (internal) as well as from family and surrounding environment (external). The data obtained show that the patterns or types of motivation possessed by these two groups tend to differ. Fresh graduates tend to have learning motivation based on four aspects: self-enrichment, job-seeking capital, filling leisure time, and competency enhancement. Meanwhile, students with work experience are motivated to continue their education at the postgraduate level based on self-development, institutional demands, competency enhancement, and as an opportunity for salary increase.